Estudo do método de síntese de materiais com estrutura perovskita nas características estruturais e na remoção do corante azul de metileno - Ribeiro, Joenesson Fílip Santos (2019)
In the last decades several synthesis methods have been used to prepare mixed oxides with perovskite structure aiming to optimize their characteristics and properties. In the present work, LaNiO3 type materials with perovskite structure were prepared from the following methods: modified protein using gelatin as a complexing agent, mechanosynthesis and combustion method in the heating plate and microwave. The obtained materials were applied in the removal of methylene blue dye in aqueous medium. After synthesis the sample obtained by the modified protein method was heat treated at 350 °C. All materials obtained by the different methods were then calcined at 900 °C for two hours. The materials were characterized by Fourier Transform Infrared (FTIR) vibrational spectroscopy, X-ray diffraction (XRD), nitrogen adsorption at 77 K, and zero charge potential (PCZ). FTIR analyzes showed the metal-oxygen bonds for all materials. XRD analysis indicated the presence of the perovskite phase for all synthesis methods after calcination. The samples calcined at 900 °C were applied as adsorbents to remove methylene blue dye in aqueous solution. Among the different synthesis methods used, the material synthesized by mechanosynthesis presented higher efficiency in the dye removal. After the removal tests, XRD analysis showed that the perovskite structure remained at the end of the process, allowing a reuse of the adsorbent after calcination. Reuse tests indicated that materials still retain a high potential for removal.